A study on digital piracy of movies: internet users’ perspective - Liang, Johan; Phau, Ian (International Management Development Association, 2011)
This study investigates the factors influencing “illegal” downloading of movies from the Internet. Specifically, it examines how personal factors (“habitual behaviour”, “affect”, “self efficacy” and “moral judgement”) and social factors (“facilitating conditions” and “social factors”) influence “attitudes towards illegally downloading movies”. Self Control Theory, Theory of Planned Behavior (TPB), and Neutralization Theory will be used to as theoretical foundation to explain the research model in this study. A number of implications for businesses will be discussed, suggestions for future research are reviewed and the main contributions of the study will also be delineated.